Meningkatkan Hasil Belajar Servis Bawah Permainan Bola Voli Menggunakan Metode Demonstrasi Pada Siswa Kelas VII SMP Negeri 30 Buru - Umasugi, Rosmayanti; Syaranamual, Jusak; Souisa, Mieke (Prgram Studi Pendidikan Jasmani Kesehatan dan Rekreasi, FKIP Universitas Pattimura, 2023)
The identification, it can be explained that motivation students to use under serve in volleyball game is lowest, because facilities and equipment is not compare to the number of students. This research uses a demonstration method. The aim in this research is find out result of the bottom serve in volleyball games with the demonstration method at SMP Negeri 30 Buru. Data of classroom action research (PTK) was carry out in two cycles, there are cycle 1 and cycle II. Data for each cycle is obtained from the results of observations and performance tests based on indicators an assessment rubric. This score is final complete or not to continue in cycle II. serving volleyball in class VII SMP Negeri 30 Buru. the results of student ability tests during two cycles, namely cycle I 73.93%, cycle II 84.66%, there was an increase of 11% in the use of the demonstration method by teachers from cycle I to cycle II, an increase of 11%. improved. This shows that teacher's success in learning process.